Detection of Mycobacterium tuberculosis by GeneXpert in Smear Negative Presumptive Case of Pulmonary Tuberculosis Patients (Tribhuvan University Journal of Microbiology, 2023)
Objectives: This study aimed to determine the efficacy of GeneXpert to identify smear-negative pulmonary tuberculosis patientsMethods: A cross-sectional descriptive study was carried out among 166 outpatients who visited the laboratory Unit of Jalal-Abad Tuberculosis Centre located in Kyrgyzstan. Non-probability; convenient sampling type was used to collect the data for the study. Standard Procedure that was described by the operating manual (Cepheid Inc, Sunny Vale USA) of GeneXpert machine was used for the procedure.Results: Out of 166 smear negative cases, 45 (27.1%) cases were shown to be positive by GeneXpert. Among the 45 cases, the GeneXpert analysis revealed that 60% were sensitive towards rifampicin and only 24.4% were resistance, remaining were intermediate.Conclusion: This research shows that Xpert MTB/RIF can identify TB in patients with negative smear tests with a good detection rate, and results would be available the same day, avoiding patient loss and treatment delays.